Progress on effects of BaP exposure on female reproductive system and pathogenic mechanisms - Qianqian GAO; Xiaoling FENG (环境与职业医学)
Benzo[a]pyrene (BaP) is the most abundant environmental pollutant among polycyclic aromatic hydrocarbons (PAHs), and is widely distributed in air, water, soil, barbecue, and fried foods. Human beings are inevitably exposed to BaP. Studies have shown that BaP is reproductively toxic and is involved in diseases related to the female reproductive system by affecting the secretion of ovarian hormones, interfering with the function of ovarian mitochondria (affecting oocyte maturation), affecting embryo development (interfering with the migration of trophoblast cells, invasion, proliferation, apoptosis) and the process of metaplasia. This article summarized the research progress on the associations between BaP exposure and female reproductive function, miscarriage, and reproductive system tumors based on relevant studies at home and abroad in recent years, with a view to providing a basis and new direction for future research.